Association of the IL‐6R rs2228145 polymorphism with diabetic nephropathy: A case‐control study - Izakovicova, Pavla; Slezakova, Simona; Deissova, Tereza; Poskerova, Hana; Borilova Linhartova, Petra; Dusek, Ladislav; Kankova, Katerina; Izakovicova Holla, Lydie (Journal of diabetes investigation, 2025)
ABSTRACT Introduction The pathogenesis of diabetes mellitus (DM) and its complications has been previously linked to elevated levels of interleukin‐6 (IL‐6); IL‐6 triggers intracellular pathways through interaction with the IL‐6 receptor (IL‐6R). This study aimed to determine the association of single nucleotide polymorphisms (SNPs) IL‐6 −597G/A (rs1800797), −572G/C (rs1800796), −174G/C (rs1800795), its receptor (IL‐6R) Asp358Ala (+48892A/C, rs2228145) and DM or its complications in the Czech population. Materials and Methods In total, 669 subjects participated in this case‐control study, including 167 controls, 119 patients with type 1 DM (T1DM), and 383 patients with type 2 DM (T2DM). The subjects were monitored for glycemia, glycated hemoglobin, lipid profile, glomerular filtration rate (GFR), and common complications, such as diabetic nephropathy (DN), retinopathy (DR), (poly)neuropathy (DPN), and periodontitis (P). Results Frequencies of the IL‐6 and IL‐6R alleles or genotypes, and IL‐6 haplotypes were similar between the controls and the patients with T1DM or T2DM (P > 0.05). However, lower values of GFR were observed in diabetic patients with IL‐6 −174CC homozygotes compared to other (CG and GG) genotypes (P ≤ 0.05). In addition, the IL‐6R Asp358Ala variant was associated with DN (P = 0.031, OR = 1.74, 95% CI: 1.05–2.89). After subclassification according to the type of DM, the significant association of the IL‐6R polymorphism with DN was only found in T1DM (P = 0.013, OR = 2.90, 95% CI: 1.25–6.71). Conclusions This study implies a significant relationship between the IL‐6R Asp358Ala polymorphism and DN in Czech T1DM patients.